M11 The impact of respiratory speech and language therapy on patients' cough related symptoms. (15th November 2016) - Haines, J; Slinger, C; Vyas, A; Chua, S; Fowler, SJ
Abstract : Introduction: Unexplained chronic cough may persist despite systematic evaluation and medical treatment of relevant comorbidities. Currently there are no effective, acceptable anti-tussive agents for the treatment of such patients and significant physical, social and psychological morbidity is described. The role of non-pharmacological treatment approaches and specifically speech and language therapy have been reported to be effective. In our specialist tertiary airways service, all patients with unexplained chronic cough greater than 8 weeks in duration, remaining unexplained after investigation and supervised therapeutic trials, are referred for respiratory speech and language therapy (rSLT). Aims: To determine the effect of rSLT on the Leicester Cough Questionnaire (LCQ) and establish specifically whether the impact occurs across each of the described domains: physical, psychological and social. Methods: We included retrospective data from all patients with unexplained chronic cough who completed rSLT between January and June 2016, and who had LCQ data available before and after treatment. Results: Sixteeen full data sets [69% female; median (range) age 58 (35–73) years] were available for analysis; rSLT median = 4, (range = 3–6) sessions. There was overall improvement in LCQ from median (range) 13.0 (7.0–18.0) pre to 17.4 (8.0–21.0) post rSLT [minimal important difference (MID) 1.3; Wilcoxon's signed rank p < 0.001]. Each domain improved post rSLT: physical from 4.7 (3.0–7.0) pre to 6.0 (2.0–7.0) post (MID 0.2; p = 0.004); psychological: from 4.0 (1.0–6.0) to 6.1 (3.0–7.0) (MID 0.8; p = 0.001); and social from 4.0 (2.0–7.0) to 5.7 (3.0–7.0) post (MID 0.2, p = 0.001). Individual answers to 10 of the 19 LCQ questions showed statistically significant improvements. Conclusion: These preliminary data indicate that rSLT improves cough related symptoms similarly cross all domains. Further investigation is needed to inform which aspects of patients' cough-related symptoms do/do not improve with therapy to guide treatment refinement. Specifically, closer investigation of response to individual LCQ questions may lead to improvements in therapeutic strategies.